The influence of sintering temperature to the physical properties of P/M Co-Cr-Mo (F-75) alloy - Zuraidawani, Che Daud (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.